2016
DOI: 10.1189/jlb.5bt1215-556rr
|View full text |Cite
|
Sign up to set email alerts
|

At the Bench: Chimeric antigen receptor (CAR) T cell therapy for the treatment of B cell malignancies

Abstract: The chimeric antigen receptor (CAR) represents the epitome of cellular engineering and is one of the best examples of rational biologic design of a synthetic molecule. The CAR is a single polypeptide with modular domains, consisting of an antibody-derived targeting moiety, fused in line with T cell-derived signaling domains, allowing for T cell activation upon ligand binding. T cells expressing a CAR are able to eradicate selectively antigen-expressing tumor cells in a MHC-independent fashion. CD19, a tumor-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 59 publications
0
6
0
5
Order By: Relevance
“…For instance, CAR-T cells were shown to be potent against CD19-expressing hematologic tumors in several trials (103, 104). However, the safety of CAR-T cells remains a major obstacle, and CARs must be optimized to increase efficacy and limit treatment-related morbidities due to cytokine-release syndrome (105). Up to now, the use of CAR-T cells for treating solid tumors has been limited by the lack of appropriate tumor antigens (106).…”
Section: Exploiting the Nkg2d/nkg2d-l Pathway For Cell Therapy-based mentioning
confidence: 99%
“…For instance, CAR-T cells were shown to be potent against CD19-expressing hematologic tumors in several trials (103, 104). However, the safety of CAR-T cells remains a major obstacle, and CARs must be optimized to increase efficacy and limit treatment-related morbidities due to cytokine-release syndrome (105). Up to now, the use of CAR-T cells for treating solid tumors has been limited by the lack of appropriate tumor antigens (106).…”
Section: Exploiting the Nkg2d/nkg2d-l Pathway For Cell Therapy-based mentioning
confidence: 99%
“…Chimeric antigen receptor (CAR)-T-cell therapy exploits an antibody-dependent, major histocompatibility complex鈥搃ndependent antigen recognition paradigm to specifically target cancer cells using genetically engineered T cells. It is one of the most sought-after tools for treating hematologic malignancies ( Daniyan and Brentjens, 2016 ; Posey et al, 2016). Recently, extensive studies have revealed the molecular mechanisms of CAR-T activation, such as charged lipids and ions鈥搑egulated CD28 conformation and signaling ( Yang et al, 2017 ) and LAT-independent formation of CAR microclusters ( Dong et al, 2020 ); SILAC-based phosphoproteomics revealed unique signaling circuits of CAR-Ts, and the distance of synapse from CAR-T/tumor cells was found to affect T-cell function ( Xiao et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Chimeric antigen receptor (CAR) T cell therapy in DLBCL and its variants provides a new treatment option for patients who relapse after 2 or more lines of therapy. Commercially available CAR T cells are produced by transducing autologous T cells with a gene encoding a hybrid receptor comprising an extracellular target binding domain, a transmembrane domain, and intracellular signaling domains that can eliminate CD19 expressing tumor via effector and cytolytic processes [6,7]. Second-generation CD19-directed CAR T cell therapies, those containing both a CD3-z signaling domain and a costimulatory domain, were evaluated in relapsed/refractory B cell lymphomas, and durable objective responses were observed in single-arm, multicenter, pivotal phase 2 trials.…”
Section: Introductionmentioning
confidence: 99%